Redo Operation for Cerebrospinal Fluid (CSF) Leak After Spine Surgery - Nawaz, Anum; Fatima, Hania; Nawaz, Farzeen; Laghari, Altaf Ali (Biological and Clinical Sciences Research Journal, 2025)
Cerebrospinal fluid (CSF) leak is a recognized complication following spine surgery and may result in the need for a secondary or “redo” operation. Early identification and effective management of such leaks are essential to prevent morbidity and optimize recovery. However, local data on the frequency and predictors of redo operations for CSF leaks in Pakistan remain scarce. Objective: To determine the frequency of redo operations for CSF leaks following spine surgery among patients admitted at The Aga Khan University Hospital, Karachi. Methods: This descriptive cross-sectional study was conducted at The Aga Khan University Hospital, Karachi, from July 7, 2024, to January 7, 2025. Ethical approval was obtained from the institutional review board. A total of 50 patients aged 18 to 80 years, of either gender, classified as ASA I–III, who developed a CSF leak within three months of spine surgery, were enrolled through non-probability consecutive sampling. Patient records were reviewed for postoperative complications, including CSF leak, swelling, wound dehiscence, and surgical site infection. The primary outcome was the frequency of redo operations for CSF leak. Data were analyzed using SPSS version 26, and a chi-square test was applied to assess associations, with p < 0.05 considered statistically significant. Results: Of the 50 patients, 27 (54%) had no postoperative complications. CSF leak with swelling occurred in 3 patients (6%), CSF leak alone in 5 (10%), and swelling alone in 3 (6%). Wound dehiscence was seen in 8 patients (16%), and surgical site infection in 5 (10%). Redo operations were required in 16 patients (32%). At the three-month follow-up, all wounds had healed, except for one patient who had residual swelling. Redo surgery was not significantly associated with age (p = 0.827), gender (p = 0.658), or spinal level involved (p = 0.116), although lumbar involvement accounted for the highest number of cases (n = 8). Conclusion: The findings demonstrate a considerable frequency of postoperative complications and redo surgeries among patients experiencing CSF leak after spine surgery. These results underscore the importance of refined surgical techniques, heightened intraoperative vigilance, and rigorous postoperative follow-up to reduce the incidence and enhance patient outcomes.